(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper intends to bring out the elements of contemporariness in Girish Karnad’s popular mythological play “Yayati”. The main plot of the play “Yayati” written by Girish Karnad, an Indian playwright, is adopted from the ‘Adiparva’ of Mahabharata. Yayati, a powerful king of Kuru dynasty, has a strong obsession towards youthfulness and worldly pleasures. He marries Devayani, Shukracharya’s daughter, but in a fit of lust, he molests Sharmishtha. This makes Shukracharya angry and a curse falls on him that he would lose his youth and become decrepit. The idea of losing his youth is extremely painful for him to bear as he cannot resist the temptation of sensual pleasure. However, the intensity of the curse is lessened when Puru, his son, visits Shukracharya. If any person is ready to give his youth to Yayati, in exchange of his old age, he could enjoy the everlasting youthfulness again. Puru, the youngest son of Yayati accepts his old age in exchange of his youth but this decision forces his wife Chitralekha to commit suicide. The death of Chitralekha awakens the sense of rationality in Yayati and he again takes back his old age from Puru and restores his youthfulness. Karnad skilfully relates the characters, incidents and circumstances of the ancient myth to contemporary society. To conclude, we can say that Karnad weaves the web of the ancient mythological story in modern social context. Like Yayati, even the modern man has extreme fascination for material and sensual pleasures. In his pursuit of worldly pleasures, he ignores spiritual values and morality.